Reply to "Comment: On the nature of 'unconventional twins' in magnesium". (February 2023) - Cayron, Cyril
Abstract: We agree with Lin et al.'s comment Lin et al.'s (2022). The interpretation we proposed to explain the twins formed in a single crystal of magnesium (Cayron and Logé, 2018) was not correct.